Effect of Carbon Content on Bainite Transformation Kinetics and Microstructure of 4140/4150 Steels - Zhu, Jian; Sun, Xichen; Barber, Gary; Han, Xue; Qin, Hao (European Scientific Journal, ESJ, 2019)
4140 steel and 4150 steel are different only in their carbon content. A comparison between the kinetics and microstructure of the bainite transformation of both steels has been carried out under a wide range of isothermal temperatures, in which four bainite phase matrices were generated. The four phases are upper bainite, mixed upper and lower bainite, lower bainite and mixed martensite and lower bainite (lower bainite transformed under Ms temperature). The bainite transformation kinetics-morphology characteristics of the four phases were studied and compared. Kinetics behavior patterns are shown with the developed TTT diagrams and kinetics plots- (bainite volume fraction vs isothermal holding time). The upper bainite and lower bainite transition temperatures are different and the bainite reaction time span is shorter when carbon content is higher. The n values in the Johnson-Mehl- Kolmogorov-Avrami (JMKA) equation have a wider deviation when carbon content is higher, indicating more bainite reaction variation. The activation energy required for the bainite phase transformations were compared and it was found that higher activation energy is needed when carbon content is higher. The subtle microstructure morphology differences are illustrated. This work will aid future development of 4140/4150 steels with bainitic microstructures having improved mechanical properties.